Serious Human Right violation victims/ International crimes and transitional justice mechanisms - Gamarra Herrera, Ronald Alex (2016)
This article discusses, in a general manner, the most important transitional justice mechanisms at which victims of serious human rights violations, constitutive of international crimes such as crimes against humanity, can participate. The analysis is mainly conducted in the light of international law areas such as international human rights law and international criminal law. Transitional justice mechanisms are examined under two categories: transitional justice mechanisms that are mainly of a retributive nature and those that are mainly of a restorative kind. In each category, possibilities, advantages, challenges and limitations faced by the victims of serious human rights violations/international crimes are examined. Some concluding remarks are provided.